Lexicon development for the sensory description of rye bread. Issue 1 (24th October 2018) - Tran, Thao; James, Meetha Nesam; Chambers, Delores; Koppel, Kadri; Chambers, Edgar
Abstract: Rye bread constitutes a major part of the Northern European cuisine and is known for its flavor versatility. Due to the large flavor difference between rye bread from Northern Europe and the United States, this study was designed to develop and evaluate a lexicon which acts as a tool for understanding the flavor profile of rye bread consumed in the United States and Northern Europe. A highly trained panel developed, defined, and referenced a lexicon with 28 flavor attributes using a consensus descriptive analysis method with 32 Northern European and U.S rye bread. The lexicon was tested with 18 representative samples. The data were analyzed using correlation analysis, principal component analysis, and cluster analysis. The results confirmed the high versatility in flavor among rye breads and revealed clear differences between Northern European rye breads and the U.S rye breads. Northen European rye bread flavor was spread over a wider flavor range than the U.S. products, and scored higher in sweet, overall grain, bran, and rye than U.S. rye breads. Practical applications: The development of this lexicon for rye bread can help researchers to better understand the flavor profile of rye bread and support manufacturers in differentiating their products from competitors as well as improving existing products on the market.